Kinetic study of thermal degradation of chitosan as a function of deacetylation degree. (1st July 2017) - Gámiz-González, M.A.; Correia, D.M.; Lanceros-Mendez, S.; Sencadas, V.; Gómez Ribelles, J.L.; Vidaurre, A.
Highlights: Coupling of the degradation of acetylated and deacetilated units in chitosan with varying deacetylation degree. Model fitting of degradation in overlapped degradation mechanisms. Previous activation energy determination by applying "free model" methods allows subsequent model fitting of TGA traces. Sestack-Berggren model yields the best fit to the experimental data in chitosan. Abstract: Thermal degradation of chitosan with varying deacetylation degree (DD) ranging between 50 and 85% was analyzed by dynamic thermogravimetric analysis at different heating rates. The present study focused on the temperature range between 500 and 800 K, above water evaporation. Thermal degradation showed a main degradation stage in this temperature interval with a second stage that appeared in the weight derivative curves as a shoulder in the high temperature side of the main peak with increasing intensity as the DD decreased. The Kissinger and isoconversional Ozawa-Flynn-Wall models were employed to evaluate the Ea of both thermal degradation processes. Different kinetic models were tested to computer simulate the thermogravimetric traces calculating the model parameters with a non-linear least squares fitting routine. The Sestack-Berggren model allowed reproducing accurately the overlapping of the two degradation mechanisms and calculating the mass fraction lost in each of them revealing the coupling between the two degradation mechanisms.